Pengaruh Booklet sebagai Sarana Peningkatan Pengetahuan Remaja Putri dalam Pencegahan Anemia - Hayati, Fatihatul; Maharani, Sri; Safitri, Safitri (Universitas Baiturrahim, 2025)
Anemia in adolescents is caused by several factors including low intake or entry of iron and other nutrients into the body such as vitamin A, vitamin C, folate, riboflavin, B12, and errors in consuming iron, for example when consuming iron together with other substances that can interfere with the iron absorption process. Pineapple (Ananas) is included in the Bromeliaceae family and is one of the fruits that can increase iron absorption in the intestine. Pineapple plants have long been cultivated by farmers in Jambi Province, this plant is cultivated on a commercial scale in Tangkit village, Muaro Jambi Regency. This study aims to determine the increase in knowledge of adolescent girls about the use of pineapple fruit with an analytical research design. The population in this study were adolescent girls with a sample of 30 female students at MAN 1 Muaro Jambi, selected using a proportional random sampling technique. An increase in adolescent knowledge was obtained by 58% and there was a significant effect of the use of booklets in increasing adolescent knowledge about the use of pineapple fruit for anemia prevention with a p value of 0.001 (CI 5%). The output of this research is in the form of increased knowledge, articles in nationally accredited journals and Intellectual Property Rights (IPR) booklets which are used as media for this research.